2016
DOI: 10.1080/10286020.2016.1240169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural studies, and cytotoxic evaluation of novel ursolic acid hybrids with capabilities to arrest breast cancer cells in mitosis

Abstract: Some novel chemically modified frameworks of ursolic acid have been designed and synthesized. The key step was the cycloaddition of azidopropyl-3β-hydroxy-urs-12-en-28-oate with the appropriate C28 propargyl esters of ursolic, corosolic, asiatic, oleanolic, and betulinic acid under Click reaction conditions, and the products were obtained in 74-84% yields. In view of their intriguing structural diversity, they have been subjected to detailed 1D and 2D NMR studies and their structures are thoroughly assigned. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Due to their similar chemical structure, the biological activity and therapeutic interest of OA and UA are rather similar, which is highly related to their dose-dependent cytotoxicity profile [6]. Previous studies have shown that these triterpenes exhibited cytotoxicity in several types of cancer cell lines [6,7,8]. Besides targeting tumor cells by induction of apoptosis, oleanolic and ursolic acids also modulate the tumor environment exhibiting antiangiogenic and anti-inflammatory activities, together with antioxidant effects and cell differentiation (e.g., [3]).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their similar chemical structure, the biological activity and therapeutic interest of OA and UA are rather similar, which is highly related to their dose-dependent cytotoxicity profile [6]. Previous studies have shown that these triterpenes exhibited cytotoxicity in several types of cancer cell lines [6,7,8]. Besides targeting tumor cells by induction of apoptosis, oleanolic and ursolic acids also modulate the tumor environment exhibiting antiangiogenic and anti-inflammatory activities, together with antioxidant effects and cell differentiation (e.g., [3]).…”
Section: Introductionmentioning
confidence: 99%
“…High cytotoxicity was observed for ursolic acid derivative, 32 ( Figure 3 , Table 1 ) modified at position C-28. This compound GI 50 values was 1.4 µM against the human breast tumor cell lines (MDA-MB-231) [ 73 , 74 ]. Ursolic acid derivatives ( 33 ) ( Figure 3 , Table 1 ) containing heterocyclic fragments such as 1,2,3-triazole and 3-(methyl)-4-methyl-1,2,5-oxadiazole-2-oxide linked at position C-28 displayed the best cytotoxic activity against MCF-7 cells with IC 50 value of 1.55 ± 0.08 µM comparable to doxorubicin.…”
Section: Triazolementioning
confidence: 99%
“…This cycloaddition reaction gives 1,2,3-triazoles and has been widely used to synthesize 1,2,3-triazole-linked BA derivatives [14] (Scheme 18). This methodology allowed the functionalization of BA at positions 2 [55,59], 3 [54,60,61,62], 28 [20,26,63,64,65,66,67,68,69,70], and 30 [71,72,73], with different substrates, including peptides, approved drugs as AZT, β-cyclodextrins, sugars, and other triterpenes, as shown in the following examples.…”
Section: Click Chemistry—copper-catalyzed Azide-alkyne Cycloadditionmentioning
confidence: 99%
“…Another interesting example of the use of click chemistry to functionalize BA was reported by Pattnaik et al [65]. The authors synthesized several triterpenoid dimers linked through a 1,2,3-triazole moiety (Scheme 23).…”
Section: Click Chemistry—copper-catalyzed Azide-alkyne Cycloadditionmentioning
confidence: 99%